Evidence-Based Practices in Community Corrections: Officers’ Perceptions of Professional Relevance and Personal Competence - Wilson, Amber (American journal of criminal justice, 2022)
While the broad goals of U.S. probation and parole agencies have shifted over time, many departments have recently begun to implement evidence-based practices (EBPs) in supervision. Adoption of EBPs, however, requires the support and active participation of line-level officers. To explore officers’ perceptions of both traditional and EBP supervision measures, we surveyed probation and parole officers in seven community corrections departments across five states. Our analyses suggest that officers identify both traditional and EBP measures as relevant to their jobs, and officers generally feel very confident in their abilities to incorporate traditional and EBP measures into their supervision approaches. Moreover, several individual and work-related variables are associated with officers’ perceived competencies for several EBP and traditional measures. Further, officers tend to feel confident with multiple supervision techniques and do not separate into camps that favor traditional versus evidence-based practices. We discuss policy implications of these findings and directions for future research.